2009
DOI: 10.1136/sti.2009.036368
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence perpetration, standard and gendered STI/HIV risk behaviour, and STI/HIV diagnosis among a clinic-based sample of men

Abstract: Background:The estimated one in three women worldwide victimised by intimate partner violence (IPV) consistently demonstrate elevated STI/HIV prevalence, with their abusive male partners’ risky sexual behaviours and subsequent infection increasingly implicated. To date, little empirical data exist to characterise the nature of men’s sexual risk as it relates to both their violence perpetration, and STI/HIV infection.Methods:Data from a cross-sectional survey of men ages 18–35 recruited from three community-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 50 publications
5
67
0
1
Order By: Relevance
“…12 In addition, the psychological sequelae of partner violence (e.g., depression, suicidal ideation) as well as substance abuse, which is associated with IPV victimization, have been shown to increase sexual risk taking and thus contribute to HIV infection. 15,16 Women's risks are compounded by the fact that perpetrators of IPV are themselves at higher risk of HIV infection, being more likely than nonperpetrators to engage in HIV risk behaviors, such as partner concurrency and transactional sex, [17][18][19] and to be diagnosed with a STI/HIV. 18,20 Violent partners are also more likely to refuse condom use.…”
Section: Hiv and Ipv: Intersecting Public Health Epidemicsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In addition, the psychological sequelae of partner violence (e.g., depression, suicidal ideation) as well as substance abuse, which is associated with IPV victimization, have been shown to increase sexual risk taking and thus contribute to HIV infection. 15,16 Women's risks are compounded by the fact that perpetrators of IPV are themselves at higher risk of HIV infection, being more likely than nonperpetrators to engage in HIV risk behaviors, such as partner concurrency and transactional sex, [17][18][19] and to be diagnosed with a STI/HIV. 18,20 Violent partners are also more likely to refuse condom use.…”
Section: Hiv and Ipv: Intersecting Public Health Epidemicsmentioning
confidence: 99%
“…18,20 Violent partners are also more likely to refuse condom use. 17 Gendered power inequalities place women at a disadvantage in regard to safer sex negotiation and refusal of unwanted sexual activity and thus contribute to women's increased vulnerability to the intersecting harms of IPV and HIV. Wingood and DiClemente, adapting Connell's theory of gender and power, 21 suggest that the sexual division of labor, gendered power inequalities, and social norms regarding gender, sexuality, and HIV prevention increase women's HIV risk.…”
Section: Hiv and Ipv: Intersecting Public Health Epidemicsmentioning
confidence: 99%
“…Silverman et al [7] found that both physical and sexual violence from husbands increased HIV prevalence among married women. Some studies among heterosexual men, in which perpetration of IPV was the focus, showed a significant association with recent HIV/STI diagnosis [8,9]. In contrast, few studies have examined the association of IPV and HIV among men who have sex with men (MSM).…”
Section: Introductionmentioning
confidence: 96%
“…Health-care professionals need to be alerted to the risk factors, such as illicit drug use, highlighted by the study and be prepared to ask all patients, including men, about DV. 16 In this study, patients with children/dependants to care for were more likely to report lifetime DV. This could be related to the added stress to a relationship or people may be more likely to report DV for the sake of children.…”
Section: Discussionmentioning
confidence: 95%